Two Green Poets: A Comparative Ecocritical Study of Sepehri and Emerson - Fomeshi, Behnam Mirzababazadeh; Pourgiv, Farideh (k@ta: A Biannual Publication on the Study of Language and Literature, 2013)
Many similar subjects can be traced in world literature, among them is nature since it belongs to man/nature binary opposition. The American poet and philosopher, Ralph Waldo Emerson (1803-1882) employs nature in his works. Throughout his works, he discusses the affinity between man and nature, emphasizing how man takes advantage of it. The contemporary Iranian poet, Sohrab Sepehri (1928-1980), also makes intensive use of nature in his poems. Sepehri is proficient in using nature either in philosophical or emotional issues. Due to the significance of nature in the works or the two figures, an ecocritical reading of them is not only applicable but unavoidable. This comparative study aims at investigating different approaches towards nature employed by the two poets, emphasizing their points of difference. Although both poets employ nature in their works with romantic tendencies, the postmodern environmental ethics of Sepehri is in direct contrast to the instrumental value viewpoint held by his American counterpart.